Managing Evidence-Based Research Processes with Systematic Review and Bibliometric Analysis Methods in Covid-19 Pandemic - (:unkn) unknown (BEZMIALEM VAKIF UNIV, 2020)
Objective: This article aims to analyze different approaches to a literature review. The publications in the pandemic period were examined by bibliometric analysis method within the framework of systematic review and determined criteria. Methods: Between 01.01.2020 and 07.06.2020, research on pandemics in WOS and Scopus platforms has been examined with a comprehensive literature study. The first aim of the study is to reveal the quality of the literature research. Another goal is to analyze the results with certain criteria. The bibliometric analysis method was used to analyze the results of the research. Results: With the determined research strategy, the publications belonging to the pandemic period were analyzed comparatively with charts and tables in WOS and Scopus platforms such as country, type of publication, institution, subject area, author, the most cited publication, and the most published journals. Conclusion: Within the framework of bibliometric analysis, it is one of the top contributors in the process with the highest number of publications in the US pandemic process. Although there is no direct relationship between the intensity of spreading of the pandemic and the publications produced, these two processes have proceeded almost parallel to each other. It has been determined that the most broadcasting institutions are universities in the USA. In this process, it was seen that most of the articles were published in order to ensure the rapid dissemination of scientific information. In the fight against epidemic, it has been observed that quite a lot of publications have been produced in the field of medicine on both platforms.
Keywords: Systematic review; meta-analysis; bibliometry; research design; COVID-19; pandemic